2022
DOI: 10.1146/annurev-statistics-040120-025426
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Cap on Longevity? A Statistical Review

Abstract: There is sustained and widespread interest in understanding the limit, if there is any, to the human life span. Apart from its intrinsic and biological interest, changes in survival in old age have implications for the sustainability of social security systems. A central question is whether the endpoint of the underlying lifetime distribution is finite. Recent analyses of data on the oldest human lifetimes have led to competing claims about survival and to some controversy, due in part to incorrect statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…From being non-significantly different to 0, the authors concluded that κ should be taken as exactly zero, indicating an exponential distribution for the data, and argue from this for an unlimited human lifespan. Later ( 14 ) and ( 15 ) updated ( 13 ) with more data and analyses but ultimately still concluded in favour of an exponential model for lifetimes and an unlimited human lifespan.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From being non-significantly different to 0, the authors concluded that κ should be taken as exactly zero, indicating an exponential distribution for the data, and argue from this for an unlimited human lifespan. Later ( 14 ) and ( 15 ) updated ( 13 ) with more data and analyses but ultimately still concluded in favour of an exponential model for lifetimes and an unlimited human lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…Later ( 14 ) and ( 15 ) updated ( 13 ) with more data and analyses but ultimately still concluded in favour of an exponential model for lifetimes and an unlimited human lifespan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The topic of aging and longevity is itself a very active area. Researchers are learning about the biology of lifespan by studying bats, whales, naked mole rats, elephants, and albatrosses, among other species (Austad & Finch, 2022;Belzile et al, 2022;da Silva et al, 2022;Eisenstein, 2022;Holmes, 2021;Kaya et al, 2021;Kolora et al, 2021;Lu et al, 2021a;Reinke et al, 2022). A Seychelles giant tortoise (called "Jonathan," hatched c. 1832) is currently the oldest known living land animal.…”
Section: Longevity and Agingmentioning
confidence: 99%
“…The theory of unobserved heterogeneity and the associated frailty model (Vaupel et al, 1979) predicts a downward deviation at the oldest ages, to which only the most robust individuals in the population survive. Detecting such a deceleration in real data is not always successful (Gavrilova and Gavrilov, 2015;Newman, 2018), even though the vast majority of studies indicate that death rates at older ages increase at lower rates and can even level off (Curtsinger et al, 1992;Fukui et al, 1993Fukui et al, , 1996Carey et al, 1995;Khazaeli et al, 1998;Gampe, 2010Gampe, , 2021Rootzén and Zholud, 2017;Alvarez et al, 2021;Camarda, 2022;Belzile et al, 2022). In a frailty model setting, testing for mortality deceleration is equivalent to testing whether the non-negative frailty parameter is strictly positive.…”
Section: Introductionmentioning
confidence: 99%